The Microdosimetry Analysis of a BNCT Treatment for Liver Cancer Based on PHITS Code Simulation - Hasna Atqona Aziizah (Indonesian Journal of Physics and Nuclear Applications, 2020)
Microdosimetry Analysis of a BNCT Treatment for Liver Cancer Based on PHITS Code Simulation. Cancer is a disease characterized by the growth and spread of abnormal cells that are not controlled. Liver cancer is in second position (788,000 deaths) as the cause of death after lung cancer. In resolving this chalenge, the BNCT method can be a solution. Boron Neutron Capture Therapy (BNCT) is a therapeutic technique based on irradiation from neutrons to boron-borne cancer cells (for liver cancer using 10boronophenylalanine (10BPA)) by utilizing neutron capture interactions with Boron-10. This study aims to analyzed microdosimetry of a BNCT treatment for liver cancer in different concentration of boron using PHITS code.